Miraculin Can Contribute to a Reduction in Inflammatory Biomarkers and Cachexia in Malnourished Patients with Cancer and Taste Disorders - Ana Isabel Álvarez-Mercado; Bricia López-Plaza; Julio Plaza-Diaz; Lucía Arcos-Castellanos; Francisco Javier Ruiz-Ojeda; Marco Brandimonte-Hernández; Jaime Feliú-Batlle; Thomas Hummel; Samara Palma-Milla; Ángel Gil (Pharmaceuticals)
Background: In 2022, there were an estimated 20 million new cancer cases and 9.7 million deaths. The number of new cancer cases is expected to rise to over 35 million by 2050, marking a 75% increase from 2022 levels. Twenty to eighty-six percent of cancer patients suffer from taste disorders (TD), which are associated with an increased risk of malnutrition. Cachectic syndrome is linked to the presence and growth of tumors and leads to systemic inflammation. Synsepalum dulcificum is a plant whose berries contain miraculin, a glycoprotein that transforms sour tastes into sweet and can ameliorate TD. Objectives: To evaluate the effect of the regular intake of dried miracle berries (DMBs), a novel food containing miraculin, on biomarkers of inflammation and cachexia in malnourished patients with cancer and TD receiving systemic antineoplastic therapy. Methods: we conducted a triple-blind, randomized, placebo-controlled pilot clinical trial. Thirty-one patients with cancer of various etiologies who received chemotherapy were enrolled in this pilot study and divided into three groups. The first group received a tablet containing 150 mg of DMB (standard dose), the high-dose group received a tablet of 300 mg of DMB, and the third group received a tablet with 300 mg of the placebo for three months before each main meal. The plasma levels of several molecules associated with inflammation and cancer cachexia were measured using the X-MAP Luminex multiplexing platform. Results: We found decreased plasma levels of IFN-γ in the standard-dose group. In addition, our results suggest a downtrend of IL-1β levels in the three groups after three months of intervention (p = 0.093). Moreover, the three groups showed a reduction in tumor-derived molecule proteolysis-inducing factor/dermcidin (p = 0.021). It is important to highlight the positive correlation between IL-6 and IL-10 in the standard group, which suggests a better balance between proinflammatory and anti-inflammatory cytokines. Regardless of DMB consumption, soluble TNF receptor type II tended to decrease with treatment in patients who responded well to the antineoplastic treatment (p = 0.011). We did not find significant correlations between cytokines and sensory variables or dietary and nutritional status. Conclusions: Our results suggest that the regular consumption of a standard dose of DMB along with a systemic antineoplastic treatment could contribute to reducing inflammation and cachexia biomarkers in malnourished patients with cancer exhibiting TD. In this sense, nutritional support is crucial in the treatment of cancer cachexia. In our view, it should be considered a coadjuvant of therapeutics. Future studies on the molecular signaling pathways and specific mechanisms of action of bioactive compounds within food supplements, such as miraculin, will allow them to be used to target pathogenic mechanisms of cancer cachexia and malnutrition: NCT05486260.